KAJIAN UJI KINERJA ALAT TANAM KEDELAI IRF-01 - Isak T. Sulle; Ruland A. Rantung; Freeke Pangkerego (COCOS, 2018)
ABSTRACT       This study aims to design and make a soybean planting tool with aspects that need to be considered such as planting conditions, number of seeds per planting hole, planting distance, seed conditions when planted, and planting efficiency. The expected outcome of this research is that it can produce soybean planting tools that can be used by farmers and academics to support government programs in increasing national soybean production.      The process of designing and manufacturing tools was carried out at the Agriculture Technology laboratory and planting or testing the performance of the tools carried out in the Unsrat village of Wailan experimental village in North Tomohon District. This research began from April 8 to May 20 2019 for the manufacture of tools and the planting process was carried out on May 22, 2019 using a planting tool that had been made with a hand tractor as a towing force and 3 weeks of observation of growing soybeans. The soybean varieties grown are Dega 1 soybean variety which is the best variety according to 2017 R & D data.      Data obtained after the process of planting and observing soybeans for 3 weeks was in the form of field efficiency data of 81.57%. with the percentage of seeds growing 61.59% and the percentage of seeds not growing 38.41%. The total percentage of seed growth is closely related to the performance of the tool because the tool still has a deficiency in the metering device that has a gap with the hopper resulting in the seeds entering the gap breaking and unable to grow when planted.  Keywords : Soybean planting tools, Spacing, Dega 1, Growing seed percentage, Field efficiency, Metering device